Reaches of the region concept (2007)
The descriptive, explicative and applicative implications and perceptions of the different nuances of the concept of region are bordered on this essay; it shows, from a critic point of view, the principles beneath where the neo-liberalism is conceived, it also reveals individualism, competitiveness, productiveness and globalization as principles that disturb a regional inclusive and democratic project. The essay also points out spatial and temporal persistency’s that consolidate certain territory control practices; finally it explores some regional alternative proposals and tries to show how to apply them to impose different principles on the prevailing model.